Conservation of migratory fishes in the Amazon basin. Issue 5 (19th March 2021) - Duponchelle, Fabrice; Isaac, Victoria J.; Rodrigues Da Costa Doria, Carolina; Van Damme, Paul A.; Herrera‐R, Guido A.; Anderson, Elizabeth P.; Cruz, Rivetla E.A.; Hauser, Marilia; Hermann, Theodore W.; Agudelo, Edwin; Bonilla‐Castillo, César; Barthem, Ronaldo; et al.
Abstract: The Amazon basin hosts the Earth's highest diversity of freshwater fish. Fish species have adapted to the basin's size and seasonal dynamics by displaying a broad range of migratory behaviour, but they are under increasing threats; however, no study to date has assessed threats and conservation of Amazonian migratory fishes. Here, the available knowledge on the diversity of migratory behaviour in Amazonian fishes is synthesized, including the geographical scales at which they occur, their drivers and timing, and life stage at which they are performed. Migratory fishes are integral components of Amazonian society. They contribute about 93% (range 77–99%) of the fisheries landings in the basin, amounting to ~US$436 million annually. These valuable fish populations are mainly threatened by growing trends of overexploitation, deforestation, climate change, and hydroelectric dam development. Most Amazonian migratory fish have key ecological roles as apex predators, ecological engineers, or seed‐dispersal species. Reducing their population sizes could induce cascading effects with implications for ecosystem stability and associated services. Conserving Amazonian migratory fishes requires a broad portfolio of research, management, and conservation actions, within an ecosystem‐based management framework at the basin scale. This would require trans‐frontier coordination and recognition of the crucial importance of freshwater ecosystems and their connectivity. Existing areas where fishing is allowed could be coupled with a chain of freshwater protected areas. Management of commercial and subsistence species also needs fisheries activities to be monitored in the Amazonian cities and in the floodplain communities to allow assessments of the status of target species, and the identification of management units or stocks. Ensuring that existing and future fisheries management rules are effective implies the voluntary participation of fishers, which can be achieved by increasing the effectiveness and coverage of adaptive community‐based management schemes.